Rainfall-runoff modelling calibration on the watershed with minimum stream gage network data - Anggraheni, Evi; Sutjiningsih, Dwita; Widyoko, Jarot (International Journal of Engineering and Technology, 2018)
The hydrological model has an important role to present the accurate and reliable information for water resources management. In this research, combination of HEC-GeoHMS and HEC-HMS that adopt the SCS-CN model have been chosen to analyse the hydrological characteristic at Upper Ciliwung Watershed. Ciliwung Watershed is one of 13 watersheds that has big influence to flood management in Jakarta. Flooding is the natural hazard that occurs every year at Jakarta. One of important part of flood early warning system at Jakarta is Katulampa Weir that located at Upper Ciliwung watershed. The area of it watershed is about 150 km2 that only has one stream gauge station at Katulampa. Accurate representation of rainfall runoff modelling at this location is important in order to predict the discharge and water infrastructure design. The objective of this paper is to obtain the parameter combination of Upper Ciliwung Watershed which can produce the discharge close to the discharge observation using HEC-HMS.Â The comparison between HEC-HMS and observation gage at Upper Ciliwung Watershed was calculated by Nash-Sutcliffe Efficiency (NSE) method. Nash value of discharge simulation at Upper Ciliwung Watershed compare with the discharge observation at Katumpa Weir reach up until 0,9.Â Â Â